Microbial and toxic metal contamination in well drinking water: potential health risk in selected areas of Kohat, Pakistan. Issue 4 (21st April 2017) - Muhammad, Niaz; Banoori, Noureen; Akbar, Ali; Azizullah, Azizullah; Khan, Mumtaz; Qasim, Muhammad; Rahman, Hazir
Abstract: In this study, the load of microorganisms and concentration and daily intake of toxic metals (Cu, Zn, Cd, Pb) in drinking water sources (wells) of three towns, Mian Khail (MK), Mer Ahmad Khail (MAK) and Gari Banurian (GB), in Kohat city of Pakistan were investigated. Multifactorial analysis was conducted to determine the microbial and toxic metals load in drinking water of the investigated towns. The obtained results revealed that the fecal coliform bacteria (FCB), Salmonella, Shigella and Staphylococci were the highest in MAK followed by MK and GB. The toxic metals concentrations and their intake load in the study area was in the order: Cd > Pb > Cu > Zn. However, the concentrations of toxic elements were within the permissible limits set by the Pakistan Environmental Protection Agency (PAK EPA). The study area had a higher load of enteric pathogens such as the Shigella sp., fecal coliform and Staphylococci in the potable water wells. The redundancy analysis (RDA) illustrated that total viable count TVB, Cu, Staphylococci and FCB were higher in MAK, fungi and Shigella sp. in GB and the Pb concentration was higher in MK. It is concluded that water in the study area is fecally contaminated and can cause health hazards. It is recommended that there should be a proper monitoring of water quality in the area to improve the existing quality and prevent further contamination of drinking water in the study area.